AVALIAÇÃO DO PERFIL QUÍMICO DO ÓLEO ESSENCIAL DA Ocotea diospyrifolia (MEISN.) MEZ (Lauraceae) NO ESTADO DE MATO GROSSO DO SUL - SANTOS, E. O.; SILVA, R. C. L.; COSTA, E. R.; LOURO, G. M.; SILVA, J. C. M.; SILVA, V. S. (ANAIS DO ENIC, 2016)
-